KOMPARASI DAYA SAING EKSPOR KOPI ROBUSTA INDONESIA DAN VIETNAM MENGGUNAKAN INDEKS RCA - Simaremare, Felisha Eunike Aprilasma; Manurung, Pebrika Citra Mastiara; Susanti, Raskia; Pranoto, Rahmawati Indriani (Journal of Economics and Business Aseanomics, 2025)
The global coffee trade has intensified competition among producing countries to enhance their export competitiveness. This study aims to compare the export competitiveness of Indonesian and Vietnamese robusta coffee using the Revealed Comparative Advantage (RCA) approach. Secondary data were obtained from UN Comtrade, ITC Trade Map, BPS Indonesia, and Vietnam's GSO for the period 2014-2023. A quantitative and descriptive-comparative analysis was conducted to evaluate trends and differences in RCA values between the two countries. Results indicate that Vietnam consistently scores higher RCA values than Indonesia, reflecting a stronger comparative advantage. Vietnam's improved competitiveness is driven by production efficiency, robust logistics infrastructure, and strong policy support. In contrast, Indonesia's competitiveness is hindered by fragmented production, infrastructure limitations, and insufficient export market diversification. Strategic actions such as infrastructure improvement, farmer training, and expansion into non-traditional markets are needed to strengthen Indonesia's position in the global coffee trade.